2004
DOI: 10.1302/0301-620x.86b2.14553
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after primary hemiarthroplasty for fracture of the head of the humerus

Abstract: We have examined 167 patients who had a hemiarthroplasty for three- and four-part fractures and fracture-dislocations of the head of the humerus in a multicentre study involving 12 Austrian hospitals. All patients were followed for more than a year. Anatomical healing of the tuberosity significantly influenced the outcome as measured by the Constant score and subjective patient satisfaction. With regard to pain, the outcome was generally satisfactory but only 41.9% of patients were able to flex the shoulder ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
192
2
30

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(229 citation statements)
references
References 13 publications
5
192
2
30
Order By: Relevance
“…In recent years, good pain relief has been consistently reported in the literature [10][11][12][13], but the post-operative shoulder range of motion and functional outcomes have been less satisfying [10][11][12]. In a multicentre, retrospective study of 167 patients by Kralinger et al [14], only 41.9 % of the patients demonstrated a postoperative forward elevation of over 90°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, good pain relief has been consistently reported in the literature [10][11][12][13], but the post-operative shoulder range of motion and functional outcomes have been less satisfying [10][11][12]. In a multicentre, retrospective study of 167 patients by Kralinger et al [14], only 41.9 % of the patients demonstrated a postoperative forward elevation of over 90°.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reports have suggested that the healing status of the greater tuberosity after shoulder arthroplasty is crucial for functional recovery of the shoulder [14][15][16][17][18][19][20][21]. In a study by Tanner and Cofield [22], post-operative displacement of the greater tuberosity was thought to be the most common complication after shoulder arthroplasty for the treatment of proximal humeral fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher complication rates have been seen in patients who underwent arthroplasty after failure of initial fracture fixation than in those who underwent humeral head replacement as the primary fracture treatment 29 . However, poor results are also seen in patients who undergo primary arthroplasty for the treatment of proximal humeral fractures 30,31 , particularly with regard to tuberosity malunion or nonunion 32,33 . Percutaneous pinning may offer the advantages of excellent reduction and union rates, preservation of rotator cuff function, and a lack of intra-articular destruction, allowing better results after revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this subset of individuals surgical treatment is recommended [5]. The widely accepted treatment of severely comminuted intra-articular proximal humeral fractures is hemi-arthroplasty or total shoulder arthroplasty [6,7]. Several surgical treatment options, such as closed reduction and percutaneous fixation [8], open reduction and internal fixation with a variety of constructs [9][10][11][12][13], proximal humeral intra medullary nailing [14] and shoulder arthroplasty [15], have been used with relatively good outcomes.…”
Section: Introductionmentioning
confidence: 99%